Mathematical modelling of cell cycle and telomere dynamics - Hirt, Bartholomäus V. (2013)
The eukaryotic cell cycle primarily consists of five phases, namely a resting state, G0, and four cycling phases G1, S, G2 and M phase, with cells progressing in this order before dividing into two cells back in phase G1. Understanding how a drug affects the cell cycle can give insight into the drug's mechanism of action and may assist research into potential treatment strategies. The pentacyclic acridinium salt RHPS4 (3,11-difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl] acridinium methosulfate) is an attractive agent because it is potentially cell-cycle specific and inhibits the activity of telomerase, an enzyme known for its role in cellular immortalisation in human cancer. The precise mechanism of action of the drug on the cell cycle dynamics, however, remains unclear.